PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. SISCOM TECHNOLOGIES - Adiky Dwi Pangestu; Muhammad Gandung (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The purpose of this study is to determine the effect of Competence and Compensation on Employee Performance both partially and simultaneously at PT. Siscom Technologies. This research method uses a quantitative method. The data collection methods used are primary and secondary data. The sampling technique used is saturated sampling and the sample obtained in this study amounted to 61 respondents. Data analysis is performed using SPSS version 26. The analysis techniques used are validity test, reliability test, classical assumption test, normality testing, multicollinearity testing, heteroscedasticity testing, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, coefficient of determination test, and hypothesis test. Partial hypothesis test of the competency variable (X1) obtained a t-value > t-table (4.784 > 1.671) and a significance value of 0.000 < 0.05. This means that competency (X1) has a significant effect on employee performance (Y). Partial hypothesis testing of the compensation variable (X2) obtained a t-value > t-table (8.338 > 1.671). This means that compensation (X2) has a significant effect on employee performance (Y). Simultaneous hypothesis testing obtained an fcount > ftable (36.564 > 3.156) and a significance value of 0.000 < 0.05. Therefore, it can be concluded that competence (X1) and compensation (X2) have a significant simultaneous effect on employee performance (Y). Determination obtained an R square of 0.558, meaning that the variables of work competence and compensation together have an influence contribution of 55.8% of employee performance. While the remaining 44.2% was influenced by other factors that were not studied in this study.